Performance of cropping systems based on winter maize (Zea mays) under irrigated condition - SIDHU, M S; SHARMA, B D; SHARMA, R K; SINGH, SUKHVINDER (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was carried out at Ludhiana during 1987-88 to 1990-91 (0 evaluate the production potential of 10 winter maize (Zea mays L.)-based cropping systems. Winter maize gave higher grain yield of 4994 and 4 712 kg/ha when raised after groundnut (Arudzis hypogaea L.) and pigeonpea [cajanus cajan (L.) Millsp.] respectively, but gave low yield (4 023 kg/ha) after rice (Oryza sativa L.). Winter maize (transplanted) after potato (Solanum tuberosum/ L.) gave significantly higher grain yield (4 380 kg/ha) thanwhen it followed toria [Brassica rapa (L.) Thell. emend, Metzger var napus L.; syn Brassic campestris L. ssp oleifera (Metzger) Sinsk, var toria]. On calculation the winter maize (ransplaned)-pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stunlz] for fodder-potato system gave the highest winter maize-equivalent yield (29.67 tonnes/ha), gross income (Rs 65 263/ha). net income (Rs 27 340/ha) andproductivity efficiency (l 02.3 kg/ha/day). Winter maize-greengram (Phaseolus radiatus L.) or sunflower (Helianthus annuus L.) system gave low winter maize-equivalent yield (5.7 and 6.9 tonnes/ha) and gross income (Rs 12 506 and 15 180/ha), and resulted in a loss of Rs 2 225 and 2 283/ha respectively. Land-use efficiency was highest (93.9%) in winter rnaize-pige, mpea, followed by winter maize-groundnut and was lowest in wheat (TriticumÂ  aestivum L. emend. Fiori & Paol.)-maize. Cropping system having legume or potato as one of the components increased the organic carbon and available P and K status of the soil.